2021
DOI: 10.1097/mao.0000000000003463
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation Can Improve Auditory Skills, Language and Social Engagement of Children With Autism Spectrum Disorder

Abstract: Objective: To review outcomes of cochlear implantation (CI) in children diagnosed with autism spectrum disorder (ASD). Study Design: Retrospective case review and parent survey. Setting: Tertiary care children's hospital. Patients: Thirty children with ASD who underwent CI between 1991 and 2018. Mean age at CI ¼ 3.5 years (0.8-11.8), mean age at diagnosis of ASD ¼ 5.1 years (2.0-15.0) (22/30 diagnosed after CI), mean follow-up ¼ 10.5 years (1.4-21.6). Parents of 7 children returned a survey. Intervention: Unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The CI can benefit hearing-impaired children also diagnosed with ASD, although all studies included in this review reported worse results for that population than those observed in children without additional disabilities 7,9,10,[18][19][20][21][22][23][24][25][26][27][28][29][30] . There is a series of reasons for such differences in the results between different populations, and they include the presence of learning and communicative disorders, associated motor impairment, sensory sensitivity, among other disorders observed in children with ASD, regardless of the presence of hearing impairment 23 .…”
Section: Reported Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…The CI can benefit hearing-impaired children also diagnosed with ASD, although all studies included in this review reported worse results for that population than those observed in children without additional disabilities 7,9,10,[18][19][20][21][22][23][24][25][26][27][28][29][30] . There is a series of reasons for such differences in the results between different populations, and they include the presence of learning and communicative disorders, associated motor impairment, sensory sensitivity, among other disorders observed in children with ASD, regardless of the presence of hearing impairment 23 .…”
Section: Reported Resultsmentioning
confidence: 79%
“…From the 16 included studies, most of them were conducted in the United States of America (USA) (n=4) 7,18,25,28 . Only one study 21 The results after the CI in children with ASD may vary, and it is possible to beneft from the device with time and proper support.…”
Section: Selection Of the Evidence Sourcesmentioning
confidence: 99%
See 3 more Smart Citations